Low-temperature plasma: an effective approach against Candida albicans biofilm - Delben, Juliana Aparecida [UNESP]; Murata, Ramiro Mendonça; Wei, Xi; Castro, Myrella Lessio; Assunção, Wirley Gonçalves [UNESP]; Silva, Nelson Renato França Alves da; Duarte, Simone (Begell House, Inc., 2014)
This study evaluated the antifungal potential of low-temperature plasma (LTP) on a 72-hour Candida albicans biofilm. A growth inhibition zone test was conducted with agar plates inoculated with C. albicans and submitted to LTP and argon application at 3 and 10 mm for 10, 30, 60, 90, and 120 seconds. The groups for biofilm assays were 60 seconds of LTP application with a tip-to-sample distance of 3 mm (LTP-3) and 10 mm (LTP-10); –application of only argon gas for 60 seconds with a tip-to-sample distance of 3 mm (Ar-3) and 10 mm (Ar-10); and no treatment. The C. albicans biofilm was grown on saliva-coated discs. The medium was replaced every 24 hours. Confocal laser scanning microscopy revealed the proportion of live and dead cells, and variable pressure scanning electron microscopy (VPSEM) showed biofilm/cell structure. No inhibition zone was observed for control and either Ar groups. For the LTP groups, a progressively increasing of inhibition zone diameter was observed for different treatment durations. The LTP-3 and LTP-10 groups presented higher proportions of dead cells compared with the Ar-3 and Ar-10 groups. VPSEM revealed cell perforations in the LTP-3 and LTP-10 groups. A short period of LTP exposure demonstrated an antifungal effect on C. albicans biofilm.
Keywords: Low-temperature plasma; Oral biofilm; Candida albicans